A panchromatic spatially resolved analysis of nearby galaxies – II. The main sequence – gas relation at sub-kpc scale in grand-design spirals. Issue 4 (23rd June 2020) - Morselli, L; Rodighiero, G; Enia, A; Corbelli, E; Casasola, V; Rodríguez-Muñoz, L; Renzini, A; Tacchella, S; Baronchelli, I; Bianchi, S; Cassata, P; Franceschini, A; et al.
ABSTRACT: In this work, we analyse the connection between gas availability and the position of a region with respect to the spatially resolved main-sequence (MS) relation. Following the procedure presented in Enia et al. (2020 ), for a sample of five face-on, grand design spiral galaxies located on the MS we obtain estimates of stellar mass and star formation rate surface densities (Σ⋆ and ΣSFR ) within cells of 500 pc size. Thanks to H i 21cm and 12 CO(2–1) maps of comparable resolution, within the same cells we estimate the surface densities of the atomic (ΣH i ) and molecular ($Σ _{\rm {H_2}}$ ) gas and explore the correlations among all these quantities. Σ⋆, ΣSFR, and $Σ _{\rm {H_2}}$ define a 3D relation whose projections are the spatially resolved MS, the Kennicutt–Schmidt law and the molecular gas MS. We find that $Σ _{\rm {H_2}}$ steadily increases along the MS relation and is almost constant perpendicular to it. ΣH i is nearly constant along the MS and increases in its upper envelope. As a result, ΣSFR can be expressed as a function of Σ⋆ and ΣH i, following the relation log ΣSFR = 0.97log Σ⋆ + 1.99log ΣH i − 11.11. We show that the total gas fraction significantly increases towards the starburst regions, accompanied by a weak increase in star formation efficiency. Finally, we find that H2 /H i varies strongly with the distance from the MS, dropping dramatically in regions of intense star formation, where the UV radiation from newly formed stars dissociates the H2 molecule, illustrating the self-regulating nature of the star formation process.